DESTRUCTION OF BRAKE PADS FRICTION MATERIALS - Volchenko, Dmytro; Kindrachuk, Myroslav; Zhuravlyev, Dmytro; Andreychikov, Yevgen; Burava, Oleksandr (Problems of Friction and Wear, 2023)
The materials of the article include the following issues: thermal shrinkage of polymer friction lining materials; destructive processes in materials of friction linings; discussion of the results.The increase in the thickness of the friction lining of the brake under bilateral thermal influence depends on the amount and intensity of release of liquid and gaseous products of pyrolysis of the binder (hence, the pressure of gases in the pores of the material close to the surface), as well as on the presence and number of pores in the material, which contribute to reducing the pressure in the pores and reducing the possibility of micro-explosions. The increase in the thickness of the tested overlays in the heated state did not exceed 0.8% (and for some materials it has a negative value), which is significantly less than the recommended values (no more than 2.5%, and for the cooled state no more than 2.0% due to various their rates of flow. Transformation of energy levels of different types of contacts formed by variable contact areas of changing microprotrusions on working surfaces to electrothermomechanical frictional interaction of friction pairs of brakes. Stabilization of lining sizes can be achieved by using a more heat-resistant binder, choosing the optimal composition of components, passing structuring processes during heating and cooling. Thermal treatment of products after forming, introduction of components that prevent the burning of the binder, etc., as well as the creation of compositions with a porous structure of the material. The use of heat treatment in the thickness of the overlay after forming must be thoroughly justified , because the equipment used for it , bulky, low-performance, very energy-intensive and requires complex equipment for cleaning from harmful secretions. Research conducted by scientists of the companies and other authors show that the presence of a polymer binder in the composition of the friction composition determines the significant influence of the temperature-time factor on the entire complex of physical and mechanical properties, and this influence has a twofold nature . In the deeper and less heated layers of the material, the processes of further structuring and hardening of the binder take place, accompanied by the strengthening of the material with thermal shrinkage. Complex physicochemical processes of oxidative decomposition, cracking and pyrolysis take place on the friction surface under conditions of high temperatures, accompanied by abundant release of liquid and gaseous products. Organoleptically, this is determined by the appearance of a smell, abundant smoke formation and characteristic crackling (micro-explosions). In conditions of difficult removal of gaseous products, due to the close contact of the working surface of the lining with the counterbody, as well as the presence or absence of pores in the material, an increase in the thickness of the lining ("swelling") is possible. In addition, during heating and cooling, the thickness of the lining increases or decreases due to thermal expansion. Thus, the change in the geometric dimensions of the lining is determined by the sum of the dimensions of the change in its thickness, associated with the thermal expansion of the material and the structural changes occurring in the material.